2013
DOI: 10.1097/scs.0b013e31828f28f3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Epidemiological Profile of Patients With Dentofacial Deformities Who Underwent Orthognathic Surgery

Abstract: The present study aimed to establish the profile of patients who underwent orthognathic surgery in a private clinic by evaluating their demographic characteristics, their facial types, and aspects related to the surgical procedures that were performed. The sample consisted of 419 medical records from male and female patients aged 15 to 62 years who underwent orthognathic surgery between 2001 and 2011. A single examiner collected data by evaluating a database of information extracted from medical records, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
0
7
1
1
Order By: Relevance
“…Generally, a higher frequency of OS is seen among women and young patients. [34][35][36] In addition, studies have a larger number of women than men. 5,11,12,37 Some studies find a female:male ratio of 2:1.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, a higher frequency of OS is seen among women and young patients. [34][35][36] In addition, studies have a larger number of women than men. 5,11,12,37 Some studies find a female:male ratio of 2:1.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of sleep apnea, genioplasty is sometimes applied for functional purposes. Castro et al [21] found a high frequency of chin surgery (76.86%) either isolated or in combination with maxillary or mandibular surgery. In this study, the prevalence of isolated genioplasty was 1%, and the prevalence of genioplasty in combination with other osteotomies was 26%, which is higher than the previously reported studies [19,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Although the dominance of 2J-OGS was coincident with the results of previous studies, the percentage of 2J-OGS in our study was somewhat higher than those reported in studies of other countries. [5][6][7][8] This could be attributed to the differences in ethnic features, since severe skeletal Class III malocclusions are more prevalent in the Asian population than in African Americans, Native Americans, and Hispanics populations. [16][17][18] When compared with the previous studies on Korean patients, both similarities and differences could be noted in the results of this study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The most prevalent skeletal discrepancy of the patients undergoing orthognathic surgery has been reported as skeletal Class III malocclusions. [3][4][5][6][7][8][9] This is also demonstrated in the Korean population, which has a high prevalence of Class III malocclusions and a negative social perception of the prognathic appearance. [9][10][11][12][13][14][15][16][17][18] Therefore, Korean has become one of the countries performing orthognathic surgery extensively in patients with skeletal Class III malocclusions.…”
Section: Introductionmentioning
confidence: 99%